2018
DOI: 10.4103/sja.sja_624_17
|View full text |Cite
|
Sign up to set email alerts
|

Pectoralis blocks for insertion of an implantable cardioverter defibrillator in two patients with Duchenne muscular dystrophy

Abstract: Patients with Duchenne muscular dystrophy (DMD) often have systemic manifestations with comorbid involvement of the cardiac and respiratory systems that increase the risk of anesthetic and perioperative morbidity. These patients frequently develop progressive myocardial involvement with cardiomyopathy, depressed cardiac function, and arrhythmias. The latter may necessitate the placement of an automatic implantable cardioverter defibrillator (AICD) insertion. As a means of avoiding the need for general anesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Relevant case reports have evaluated device implantation under PECS blocks in adults, including a PECS block with an intercostal nerve block and intravenous sedation for the subpectoral placement of a cardiac resynchronization therapy device [ 12 ], a PECS block with an intercostal block and intravenous sedation for implantable cardioverter defibrillator (ICD) insertion in young patients with Duchenne muscular dystrophy [ 13 ], a PECS block for ICD insertion in a morbidly obese patient [ 14 ], relocation of an infected cardiac pacemaker generator under a PECS block using intravenous midazolam [ 15 ], and a PECS block alone as the primary anesthetic technique without any sedation or intravenous anesthetics [ 16 ]. All studies found that the PECS block provided effective analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant case reports have evaluated device implantation under PECS blocks in adults, including a PECS block with an intercostal nerve block and intravenous sedation for the subpectoral placement of a cardiac resynchronization therapy device [ 12 ], a PECS block with an intercostal block and intravenous sedation for implantable cardioverter defibrillator (ICD) insertion in young patients with Duchenne muscular dystrophy [ 13 ], a PECS block for ICD insertion in a morbidly obese patient [ 14 ], relocation of an infected cardiac pacemaker generator under a PECS block using intravenous midazolam [ 15 ], and a PECS block alone as the primary anesthetic technique without any sedation or intravenous anesthetics [ 16 ]. All studies found that the PECS block provided effective analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, PECS block has been used exclusively for breast surgery to provide post-operative pain management or as part of multimodal analgesia to reduce opioid consumption. Relevant case reports include PECS block in combination with an intercostal nerve block with IV dexmedetomidine for the sub-pectoral implantation of a cardiac resynchronization therapy device (5), PECS block for implantable cardioverter defibrillator insertion in young patients with Duchenne muscular dystrophy with intercostal block and IV sedation (6), PECS for ICD in a super obese patient (7), and relocation of an infected cardiac pacemaker generator under PECS II block using IV midazolam (8).…”
Section: Discussionmentioning
confidence: 99%
“…Despite being used for cardiac resynchronization therapy device (CRTD) insertion, PECS cannot reliably anesthetize infraclavicular areas where the incision is usually performed; and hence, CRT insertion requires further local anesthetic infiltration. 35 PECS blocks have been incorporated as part of multimodal analgesia in breast surgeries, for which they were originally developed. They have been shown to reduce postoperative narcotic requirements, nausea, vomiting, postanesthesia care unit, and hospital LOS.…”
Section: Pecs Blocksmentioning
confidence: 99%
“…40 The same combination of PECS and ICNB had been utilized for automatic implantable cardioverter defibrillator (AICD) insertion in children with Duchenne Muscular Dystrophy (DMD). 35 Children with DMD often have compromised cardiac and respiratory function that place them at a significant perioperative risk of morbidity and mortality following general anesthesia. PECS blocks had been successfully used in super morbidly obese patients with limited cardiac and respiratory reserve.…”
Section: Pecs Blocksmentioning
confidence: 99%